2022
DOI: 10.1038/s41467-022-34981-4
|View full text |Cite
|
Sign up to set email alerts
|

Observation of a transient intermediate in the ultrafast relaxation dynamics of the excess electron in strong-field-ionized liquid water

Abstract: A unified picture of the electronic relaxation dynamics of ionized liquid water has remained elusive despite decades of study. Here, we employ sub-two-cycle visible to short-wave infrared pump-probe spectroscopy and ab initio nonadiabatic molecular dynamics simulations to reveal that the excess electron injected into the conduction band (CB) of ionized liquid water undergoes sequential relaxation to the hydrated electron s ground state via an intermediate state, identified as the elusive p excited state. The m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 70 publications
(162 reference statements)
0
6
0
Order By: Relevance
“… The broad absorption above 550 nm in the contour plot can be attributed to the absorption of the hydrated electron, which is known to absorb in the 300–1000 nm range. , The decrease in the Δ A signal of the hydrated electron at ∼700 nm may be due to plasma-induced blue shifting of the probe spectrum (Section S5). This plasma-induced blue shift prevents detailed analysis of the time-resolved Δ A spectrum to retrieve the hydrated electron formation dynamics, which is the subject of numerous previous investigations. …”
Section: Resultsmentioning
confidence: 87%
See 1 more Smart Citation
“… The broad absorption above 550 nm in the contour plot can be attributed to the absorption of the hydrated electron, which is known to absorb in the 300–1000 nm range. , The decrease in the Δ A signal of the hydrated electron at ∼700 nm may be due to plasma-induced blue shifting of the probe spectrum (Section S5). This plasma-induced blue shift prevents detailed analysis of the time-resolved Δ A spectrum to retrieve the hydrated electron formation dynamics, which is the subject of numerous previous investigations. …”
Section: Resultsmentioning
confidence: 87%
“…Under an aqueous environment, the ionization of biomolecules leads to the formation of the hydrated electron and the associated radical species, which trigger a cascade of reactions that are of fundamental importance in radiation chemistry and radiation biology. Advancements in the generation of ultrashort laser pulses and time-resolved spectroscopic techniques over the years offer a glimpse into the dynamics of these photoinduced processes. While the dynamics of the hydrated electron have been studied extensively, the ultrafast structural rearrangement dynamics of the associated radical species remain vastly unexplored. The ultrafast structural rearrangement of radical species impacts key biological processes such as long-range electron transfer in proteins and DNA. Thus, further research is needed to extend our understanding of the ultrafast structural rearrangement involving aqueous biomolecules.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, many critical aspects of the electron solvation process remain unclear. Open questions include the solvation time scale, for which studies have reported values ranging from a few hundred femtoseconds to 2 ps, ,,, the influence of the preceding ionization mechanism, ,, or the specific nature of e aq – ’s immediate precursor, , to name a few. At the origin of this general lack of consensus lies the inherent difficulty of disentangling the vibrational and electronic responses when using optical techniques .…”
Section: Introductionmentioning
confidence: 99%
“…The H 3 O + and • OH produced in reaction (1) are located very close to the position at which ionization occurred. On the other hand, the secondary electron (also called "dry" electron) created during the ionization event is ejected with a kinetic energy of a few tens of electron-volts [25][26][27], allowing it to travel, on average, a distance of the order of ~10 nm [28] before becoming thermalized and hydrated (at about 1.3 ps [29,30]). At this point in time, the hydrated electron (e − aq ), on the one hand, and H 3 O + and the • OH radical, on the other hand, are quite far apart [31][32][33].…”
Section: Introductionmentioning
confidence: 99%